The Influence of Principal Leadership and Teacher Work Discipline on Elementary School Teacher Performance - Kamalia, Kamalia; Natuna, Daeng Ayub; Sumarno, Sumarno (Journal of Educational Sciences, 2022)
Several problems were found that had an impact on teacher performance, namely teachers who did not pay attention to the students situation. Teachers sometimes came late to school, less literate with the latest learning systems, and they were less technologically literate. Teachers do not get information, there were teachers who had not completed lesson plans and do not bring a lesson plan at the time of the KBM. This study uses a descriptive correlational research method with a quantitative approach. The population of this study was the principal of a public elementary school in North Rupat which consists of SDN 1, 10, and 13 Rupat Utara. The total number of teachers is 37 people. The sample uses a saturated sample with a total of 37 people. The results of this study shows there is a positive and significant influence between Principal Leadership on Teacher Performance. The higher the organizational culture given, the higher the teacher's performance. There is a positive and significant influence between the variables of Teacher Work Discipline on Teacher Performance at SMP Rupat District. There is also a non-significant influence between the variables of Principal Leadership and Teacher Work Discipline simultaneously between the variables of Principal Leadership and Teacher Work Discipline on Performance at SDN in the North Rupat.